Parenting in the Digital Age: A Scoping Review of Digital Early Childhood Parenting Interventions in Low- and Middle-Income Countries (LMIC) - Lena Jäggi; Lena Jäggi; Stella M. Hartinger; Stella M. Hartinger; Stella M. Hartinger; Günther Fink; Günther Fink; Dana C. McCoy; Milagros Alvarado Llatance; Milagros Alvarado Llatance; Kristen Hinckley; Kristen Hinckley; et al. (Public Health Reviews)
ObjectivesThis scoping review examines the evidence and knowledge gaps regarding the effectiveness of digital early childhood parenting interventions in Low- and Middle-Income Countries (LMICs).MethodsUsing PRISMA-ScR and PICOS frameworks, we systematically reviewed studies published since 2010 from four databases, focusing on the impact of digital parenting interventions on Early Childhood Development and parent-level outcomes.ResultsOf 1,399 studies identified, 13 met inclusion criteria, evaluating digital interventions for parents of children aged 0–5 years. These interventions included digital-only and hybrid approaches, leveraging technologies for tasks such as sharing health and ECD information, reminders, group chats, or screening. Among ECD studies, three of four with parent-reported outcomes found positive effects, but none of three using direct assessments did. Parent-level outcomes, such as mental health and parenting behaviors, showed consistent positive impacts.ConclusionDigital parenting interventions are feasible in LMICs but face challenges in implementation and reaching vulnerable families. Most studies are small-scale with variable designs and outcomes. Rigorous, high-quality studies are needed to establish effectiveness and optimize implementation strategies before these programs are deployed at scale.